A broadband point source loudspeaker design and its application to anechoic chamber qualification. (July 2021) - Ghanavi, Reza; Cabrera, Densil
Graphical abstract: Highlights: A novel broadband omnidirectional source is described and tested. Emission from a small gap between two pipes approximates a point source. The source is omnidirectional (near & far fields), sufficiently powerful and stable. The source is suitable for full-range anechoic room qualification (100 Hz–20 kHz) A broadband omnidirectional source can be advantageous in detecting reflections. Abstract: A broadband point source loudspeaker, referred to as a 'gap source', is described. The source is driven by four compression drivers configured as two identical two-way sources connected to two symmetric pipe structures. The sound source radiates from a small gap between the pipe openings, yielding sufficiently powerful omnidirectional radiation in the range 100 Hz–20 kHz for anechoic room qualification in accordance with ISO 26101. For proof of concept, the source performance was compared with that of a commercial omnidirectional loudspeaker for traverses in an anechoic room. Results demonstrate that a single sound source, as described, is sufficient for anechoic room qualification in 1/3-octave bands at and above 100 Hz. The source's improved adherence to omnidirectionality is shown to be an advantage in detecting an introduced reflection in an anechoic room.